Blood pressure estimation from appropriate and inappropriate PPG signals using A whole-based method. (January 2019) - Mousavi, Seyedeh Somayyeh; Firouzmand, Mohammad; Charmi, Mostafa; Hemmati, Mohammad; Moghadam, Maryam; Ghorbani, Yadollah
Graphical abstract: Highlights: A new method is proposed for estimating the BP using only the PPG. This new method is called Whole-based method. The method uses raw values of the PPG signal for estimating the blood pressure (BP). The results show the applicability of the method into estimating blood pressure. BP estimation is noninvasive, cuff-less and calibration-free. Abstract: Background and objective: Blood pressure (BP) is one of the four vital signals that provides valuable medical information about the cardiovascular activity. In recent years, extensive studies have been conducted on non-invasive and cuff-less BP estimation using photoplethysmography (PPG) signals. PPG is a non-invasive optical method for measuring blood volume changes per pulse. In other words, the PPG waveform represents the mechanical activity of the heart. Methods: In this paper, a new method for estimating the Mean Arterial Pressure (MAP), Diastolic Blood Pressure (DBP) and Systolic Blood Pressure (SBP) is proposed using only the PPG signal regardless of its shape (appropriate or inappropriate). Our proposed algorithm called whole-based, uses raw values of the PPG signal at a given time interval for estimating the BP. In other algorithms called parameter-based, use features which are extracted from PPG signals in time or frequency domain. These features related to precise spotting in the form of the PPG signal. In fact, compared to parameter-based methods, our algorithm is independent of the form of the PPG signal. Results: Using the proposed algorithm, our results are completely met by the Association for the Advancement of Medical Instrumentation (AAMI) standard for both MAP and DBP estimations. The results are also very close to the standard boundary with an average error close to zero for SBP estimation. Also, according to the British Hypertension Society (BHS) standard, the proposed algorithm for DBP estimation got grade A, whereas it got grade B for estimation of MAP and got approximately grade C for SBP estimation. Conclusion: The results demonstrate the applicability of the proposed algorithm in estimating BP noninvasively, cuff-less, calibration-free, and only by using the appropriate or inappropriate PPG signal.